The evolution of performance management discourse in corporate strategy diagrams for public institutions. (September 2016) - Ledin, Per; Machin, David
Abstract: A specific kind of performance management model called 'Balanced Scorecard' has come to dominate the way institutions are run around the world, oriented to increasing outputs and to 'quality assurance'. Strategic diagrams emerged out of this model, claiming to break down all institutional parts and processes into a flow-chart forming a sort of road map of the role played by all parts of an organization in reaching targets. Drawing onFairclough׳s (1992) notion of the 'technologization' of discourse andVan Leeuwen׳s (2008) notion of 'the new writing' this paper applies multimodal critical discourse analysis to a sample of diagrams from a wider corpus showing how they have changed over time, becoming more abstracted and symbolic, as the performance management discourse itself has become naturalized. Highlights: There has been a profound shift in how public institutions communicate. New technologies enable an increasing codification of semiosis. In this 'new writing' semiotic resources are combined in new and more symbolic ways. Taking universities as a case we analyze strategic diagrams of performance management. We reveal how these diagrams enable monitoring in the name of quality assurance.